1994
DOI: 10.1073/pnas.91.6.2130
|View full text |Cite
|
Sign up to set email alerts
|

Expression of human apolipoprotein B and assembly of lipoprotein(a) in transgenic mice.

Abstract: The atherogenic macromolecule lipoprotein(a) [Lp(a)] has resisted in vvo analyses partly because it is found in a limited number of experimental animals. Although transgenic mice expressing human apolipoprotein (a) [apo(a)] have previously been described, they faied to assemble Lp(a) particles because of the inability of human apo(a) to associate with mouse apolipoprotein B (apoB). We isolated a 90-kilobase P1 paemid containing the human apoB gene and with this DNA generated 13 lines of tnsgec mice of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
131
1
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 31 publications
7
131
1
2
Order By: Relevance
“…Despite this limitation, studies using transgenic mice producing human Lp[a] have already contributed much to our understanding of Lp[a] synthesis (27)(28)(29)(30) and its role in atherosclerosis (31)(32)(33). Furthermore, we believe that mice may also offer an attractive model for the study of Lp[a] catabolism, because they are able to clear the lipoprotein in a way that appears to be similar to that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, studies using transgenic mice producing human Lp[a] have already contributed much to our understanding of Lp[a] synthesis (27)(28)(29)(30) and its role in atherosclerosis (31)(32)(33). Furthermore, we believe that mice may also offer an attractive model for the study of Lp[a] catabolism, because they are able to clear the lipoprotein in a way that appears to be similar to that in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Following intravenous infusion of human LDL, but not of VLDL, into transgenic mice, Lp(a) that is indistinguishable from native Lp(a) found in humans is formed. Double transgenic mice expressing both human apo(a) and human apoB-100 synthesize bona fide Lp(a) directly [36,37]. It is interesting to note that the plasma apo(a) levels were higher in double transgenic mice than in those producing only apo(a), suggesting a faster removal rate of apo(a) that is not complexed to LDL.…”
Section: Assembly Of Lp(a): the Role Of Apo(a) Structurementioning
confidence: 99%
“…Therefore, we have to use double transgenic mice with human apo (a) and human LDL to test the Lp(a) function. The previous studies showed that mice expressing the apo(a) gene developed atherosclerosis (16,17). Using this model animal, Kyutoku M et al (18) reported that DNA vaccine against apo(a) could significantly inhibit neointima formation in carotid artery ligation and concluded that the pro -atherosclerotic actions of Lp(a) could be prevented by reducing Lp(a) levels.…”
Section: Discussionmentioning
confidence: 92%